Customers' Precedence for Service Quality Dimensions in Indian Private Healthcare Setting: A Ridit Approach. Issue 4 (2nd October 2017) - Panda, Rajeev Kumar; Kondasani, Rama Koteswara Rao
ABSTRACT: Changes in demographic and sociocultural environment, improved health awareness, and information technology have considerably changed the outlook of healthcare sector in India. While both the public and the private healthcare sectors have priority of increasing access while minimizing costs, they try hard to achieve goals without letting the quality suffer. Customers with rising disposable income no longer have faith in the public healthcare system and are willing to migrate to the private healthcare sector, which is more professional, technology savvy, and trustworthy. However, there are enough loopholes in the private healthcare sector that are yet to be plugged. The purpose of this research study was to identify and assess the relative importance of the diverse service quality dimensions and prioritize them to draw meaningful conclusions. Survey responses from 370 customers were analyzed using factor analysis to find underlying relationships between the survey items. This allowed the individual items to be placed into related groups. Independently, a ridit analysis was conducted to determine the relative importance of each item to the survey respondents. Based on the ridit analysis a priority ranking was assigned to each item. An analysis was then undertaken of the degree to which the items grouped into each particular factor tended to have high or low priority rankings. The results of the study may be helpful to the managers of the private healthcare sector to focus their strategies and plan their efforts in line with the findings to gain superior customer satisfaction and retention.